Review and update about the late Triassic to Jurassic tectonics through the transition zone between the southern Central and Patagonian Andes - Folguera Telichevsky, Andres; Navarrete, Cesar; Gianni, Guido Martin; Echaurren, Andres; Fennell, Lucas Martín; Martos, Federico Exequiel; Acevedo, Eliana Belén
In the last years, a substantial change has occurred concerning previous concepts accepted for theJurassic tectonics in the area comprehended between the Patagonian and Central Andes. The previoushypothesis conceived a rather simple framework in which from the Neuquén Basin latitudes to the southinto Patagonia, a series of extensional depocenters were evolving through their mechanical and thermalsubsiding stages during incipient Pangea break up. However, in the last time, new data and ideas havedefied these hypotheses, strongly affianced in the scientific community, following pioneering proposalsof Lock (1980) and Dalziel et al. (2000). The first of these controversial premises is that Patagoniasuffered a shortening stage associated with the inland migration of a volcanic arc in Late Triassic times(Navarrete et al., 2019), while to the north crustal stretching conditions dominated south-westernGondwana. This new hypothesis considers that the Late Triassic Central Batholith constitutes amagmatic arc in central Patagonia and that a Late Triassic contractional episode developed, describedfrom field and seismic data. The second premise is that Patagonia kept suffering short pulses ofwithin-plate shortening during the Jurassic, interrupting sag stages of intra- and retro-arc basins(Navarrete et al., 2016). These discrete pulses most likely relate to a strong kinematic change anddrifting to the south registered in Gondwana at ~180 Ma, when the North Atlantic ocean started tospread, and with the initial Weddell sea opening at ~160 Ma that pushed the Patagonian platform in theopposite direction, at the time when the Karoo hot spot emplaced and expanded to the east (Müller etal., 2006). During these changes, the Liassic and Cañadón Asfalto basins in Chubut, easternvolcanogenic basins, and the North Patagonian and Deseado massifs suffered early inversion andexhumation phases. These Late Triassic to Jurassic contractional pulses thickened the crust indicatedby REE elements in Mesozoic magmas emplaced in the Patagonian ...